EKSPLORASI POTENSI DAN TANTANGAN BISNIS CV INDAH MELALUI ANALISIS SWOT: Studi Kasus Pada Perusahaan Kecil Menengah - Ari Nurcahyo Darmawan (STIE PGRI Dewantara Jombang, 2024)
Abstract This study aims to analyze the marketing strategy implemented by CV Insan Berkarya in increasing the sales of household health products. Using a descriptive approach with a survey method, data was collected through observation, interviews, and documentation, and analyzed using the SWOT method. The results show that CV Insan Berkarya's strengths lie in providing quality products, affordable prices, good service, and a strategic location. However, its weaknesses include a lack of brand positioning and limited promotion. Externally, the company faces threats from competitors offering competitive prices and superior services, but also has opportunities to retain and attract customers through good relationships. It is recommended that the company improve brand positioning, implement intensive promotion, introduce product variations, and enhance service quality and customer relations. This research provides insights for SMEs to develop marketing strategies to increase competitiveness and sales in a competitive market.